2019
DOI: 10.3892/mmr.2019.10491
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant effects of apigenin are associated with the�promotion of autophagy via the mTOR/AMPK/ULK1 pathway

Abstract: The present study aimed to investigate whether apigenin elicits antidepressant effects in depressant-like mice via the regulation of autophagy. The depressant-like behaviors were established in a chronic restraint stress model. Male BalB/c mice were subjected to restraint stress for 6 h/day for a period of 21 days, and deficits in sucrose preference, tail suspension and forced swim tests were confirmed to be improved following oral apigenin. To investigate the underlining mechanisms, the hippocampal levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…This natural flavone has been shown to exert therapeutic effects in neurological disorders and CVD [17]. Other studies showed that apigenin has hepatoprotective, antidepressant, anticancer and antihypertensive effects; it is also able to prevent autoimmune myocarditis, atherogenesis and asthma and induces beneficial action against osteoporosis, type 2 diabetes mellitus and pancreatitis [69][70][71][72][73][74][75][76][77][78][79][80]. Importantly, in addition to the involvement of apigenin in inflammation modulation, mRNA splicing regulation, cell cycle arrest and regulation of apoptosis [81], most of these findings support the hypothesis that the beneficial effects of apigenin are also attributed to its capacity to counteract oxidative stress, which is known to be a key component of many diseases, including cardiovascular, pulmonary, neurodegenerative diseases, cancer and metabolic disorders [82].…”
Section: Broad-spectrum Antioxidant Activity Of Apigenin With a Main Focus On Dysmetabolic Conditionsmentioning
confidence: 99%
“…This natural flavone has been shown to exert therapeutic effects in neurological disorders and CVD [17]. Other studies showed that apigenin has hepatoprotective, antidepressant, anticancer and antihypertensive effects; it is also able to prevent autoimmune myocarditis, atherogenesis and asthma and induces beneficial action against osteoporosis, type 2 diabetes mellitus and pancreatitis [69][70][71][72][73][74][75][76][77][78][79][80]. Importantly, in addition to the involvement of apigenin in inflammation modulation, mRNA splicing regulation, cell cycle arrest and regulation of apoptosis [81], most of these findings support the hypothesis that the beneficial effects of apigenin are also attributed to its capacity to counteract oxidative stress, which is known to be a key component of many diseases, including cardiovascular, pulmonary, neurodegenerative diseases, cancer and metabolic disorders [82].…”
Section: Broad-spectrum Antioxidant Activity Of Apigenin With a Main Focus On Dysmetabolic Conditionsmentioning
confidence: 99%
“…Endolysosome acidification may also restrict coronavirus infections by blocking the escape of viral RNA to the cytosol and promoting viral degradation in lysosomes ( Carmona-Gutierrez et al, 2020 ; Gassen et al, 2020 ; Yang and Shen, 2020 ). A number of natural compounds acidify endolysosomes and might be tested for their ability to enhance coronavirus degradation; these include spermidine and spermine ( Gassen et al, 2020 ), baicalein ( Zhu et al, 2020 ), vitamin D3 ( Hu et al, 2019 ; Daneshkhah et al, 2020 ), 17-beta-estradiol ( Lipovka and Konhilas, 2014 ; Xiang et al, 2019 ; Khan, 2020 ; Suba, 2020 ), ketone bodies ( Hui et al, 2012 ; Camberos-Luna et al, 2016 ), trehalose ( Sharma et al, 2020 ), wogonin ( Li et al, 2016 ), apigenin ( Zhang X. et al, 2019 ), and butein ( Ansari et al, 2018 ) ( Figure 2 ).…”
Section: Effects Of Endolysosome Ph On Coronavirus Infectionmentioning
confidence: 99%
“…It was reported that AP regulate autophagy. For example, AP promoted autophagy through the mTOR/AMPK/ULK1 pathway and could play an antidepressant effect [48], inhibited the growth of cisplatin-resistant colon cancer cells by inducing autophagy and apoptosis [49], and restored impairment of autophagy and downregulation of unfolded protein response regulatory proteins in keratinocytes exposed to ultraviolet B radiation [50]. Studies have suggested that p62 protein is regulated by oxidative stress and is a transcriptional target of Nrf2 [51,52].…”
mentioning
confidence: 99%